1997
DOI: 10.1524/ract.1997.77.3.149
|View full text |Cite
|
Sign up to set email alerts
|

First Aqueous Chemistry with Seaborgium (Element 106)

Abstract: For the first time, chemical separations of element 106 (Seaborgium, Sg) were performed in aqueous solutions. The isotopes 265 Sg and 266 Sg were produced in the 248 Cm + 22 Ne reaction at a beam energy of 121 MeV. The reaction products were continuously transported by a He(KCl)-jet to the computer-controlled liquid chromatography system ARCA. In 0.1 M HNO3/5 X ΙΟ -4 M HF, Sg was found to be eluted within 10 s from 1.6X8 mm cation-exchange columns (Aminex A6, 17.5±2 μπι) together with the hexavalent Mo-and W-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 33 publications
2
52
0
4
Order By: Relevance
“…It is then necessary, in order to get statistically significant result, to repeat the same experiment several hundred or even several thousand times with a cycle time of typically 1 min. These discontinuous studies were either performed manually [55,[63][64][65][66][67][68] or with the Automated Rapid Chemistry Apparatus ARCA II [69][70][71][72][73][74][75][76][77][78][79][80] or with the Automated Ion-exchange separation apparatus coupled with the Detection system for Alpha spectroscopy AIDA [81].…”
Section: Aqueous Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It is then necessary, in order to get statistically significant result, to repeat the same experiment several hundred or even several thousand times with a cycle time of typically 1 min. These discontinuous studies were either performed manually [55,[63][64][65][66][67][68] or with the Automated Rapid Chemistry Apparatus ARCA II [69][70][71][72][73][74][75][76][77][78][79][80] or with the Automated Ion-exchange separation apparatus coupled with the Detection system for Alpha spectroscopy AIDA [81].…”
Section: Aqueous Chemistrymentioning
confidence: 99%
“…Automated separations with ARCA II were performed with element 104 [75,79] [73,74,76]. ARCA II is a computer controlled apparatus for fast, repetitive High Performance Liquid Chromatography (HPLC) separations [80].…”
Section: Aqueous Chemistrymentioning
confidence: 99%
“…Preliminary results of the first chemical separations of Sg conducted with OLGA and ARCA in 1995 and 1996 have now been reported (12,13). Isothermal gas chromatography experiments on the oxychlorides were conducted with OLGA followed by unambiguous detection of 265+266 Sg via the α-decay chains.…”
Section: Renaissance and New Resultsmentioning
confidence: 99%
“…Recently, periodic tables similar to the one shown in Fig. 4 have been proposed (11)(12)(13). The first five actinides are shown in a stairstep arrangement leading from Rf down to the trivalent actinides, Am and Cm, to reflect the similarities in chemical behavior between the early actinides and the elements in groups 4 to 8.…”
mentioning
confidence: 91%
“…An additional 8 atoms of its radioactive decay product, 256 Fm, were also separated and measured. Atom-at-a-time chemical studies have now been performed on all of these elements-the first studies on Sg were reported by Schädel et al (12,13) in 1997. The chart of the known isotopes of Sg through element 112 is given in Fig.…”
mentioning
confidence: 99%